Pengaruh Kompensasi dan Motivasi Kerja terhadap Kinerja Pegawai Dinas Pendidikan Kota Bekasi - Fauzi, Ahcmad; Selvi, Evi (Peneliti.net, 2025)
This study aims to analyze the impact of compensation and work motivation on employee performance at the Bekasi City Education Office with a quantitative approach, using descriptive and verification analysis. This study involved 69 respondents selected through non-probability sampling techniques and using Microsoft Office and SPSS 25 to conduct multiple regression analysis. The results showed that compensation had an average value of 241.9 (agree category), work motivation with an average of 262.3 (agree category), and employee performance with an average of 272.9 (strongly agree category), which indicates very good employee performance. Partially, its influence on employee performance is 12.5%, while the influence of work motivation is 19.8%. Simultaneously, incentives and work motivation contribute to employee performance by 54.1%, while the other 45.9% is influenced by other variables not studied. Compensation and work motivation are proven to have a significant influence on employee performance.